Clinical features of fetal growth restriction complicated later by preeclampsia - Mitani, Minoru; Matsuda, Yoshio; Makino, Yasuo; Akizawa, Yoshika; Ohta, Hiroaki (The journal of obstetrics and gynaecology research, 2009)
Objective:  To assess the maternal and perinatal outcome of preeclampsia with fetal growth restriction (FGR) and to assess the risk factors of FGR complicated later by preeclampsia. Subjects and Methods:  A cohort of women with preeclampsia and/or FGR (n = 306) were retrospectively reviewed. First, the maternal and perinatal outcome were compared between preeclampsia with FGR (n = 37) and preeclampsia without FGR (n = 96). Second, the clinical findings of FGR followed later by preeclampsia (n = 24) were compared to FGR without preeclampsia (n = 149). Results:  The incidence of severe hypertension and critical maternal complications in women with preeclampsia with FGR was significantly higher than in those with preeclampsia without FGR. In women diagnosed with FGR, 13.8% (24/173) developed preeclampsia later. In this group, FGR was diagnosed at 28.8 gestational weeks, which was then complicated by preeclampsia at a mean of 32.6 gestational weeks, and delivered at 33.3 gestational weeks. The diagnosis of FGR was earlier and the incidence of proteinuria at entry was more common in women with FGR complicated later by preeclampsia than in those with FGR without preeclampsia (45.8% vs 4.7%; P < 0.001). Conclusions:  Preeclampsia with FGR is severe condition which can possibly adversely affect the maternal condition. About 15% of all mothers diagnosed with FGR developed preeclampsia afterwards; therefore, those with FGR are considered to be candidates for close monitoring for the clinical manifestation of preeclampsia, and those with early‐onset FGR with proteinuria may represent a high‐risk group for preeclampsia.